Strategi Pendampingan Pastoral bagi Anak di Era Digital dalam Pembinaan Karakter di Gereja Toraja Jemaat Imanuel Baturara’ Ra’Bung - Nelvi Datu Rombe (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
Considering the importance of the next generation in the church, children must be empowered to be better. Therefore, this research can be a work that provides education about the influence of technology on Sunday school children at the Imanuel Batubara' Ra'Bung church which can be used as an instrument to help them in developing better thinking patterns. The research method used is a qualitative research method with a descriptive approach to describe the reality of the reality that occurs in the field. The qualitative method is applied through library research and field analysis. The library study is applied by finding supporting theories that are relevant to the research. Furthermore, a descriptive approach is applied through interview techniques and field analysis. Interviews were conducted by the author through field research and social analysis. The theories applied by the author are theories about counseling, theories about the church and theories about social assistance. The results of this study are that Sunday school teachers and child care providers must work together to help Sunday school children know God well and also be able to lead themselves in a better direction.